Demokrasi sebagai Tindakan Politik: Proposal Filsafat Politik Hannah Arendt Menghadapi Totalitarianisme - Mikhael - Dua (Jurnal Ledalero, 2022)
Abstract:This article aims to map out Hannah Arendt’s proposal on democratic political action as a solution to the problem of totalitarianism. For this purpose, the article will consist of three parts. The first part will deal with the problem of totalitarianism as reflected in The Origins of Totalitarianism. The second part will deal with Arendt’s philosophical proposal of democracy as political action against totalitarianism as its enemy. It argues that freedom and constitution are the basis of people’s political action in public space for the sake of nation and community. The third part will deal with the problem of human rights and Arendt’s proposal of political natality. According to the principle of natality, people as subjects of politics are capable to find their own ways to preserve their own life. Human transcendence is actualized in time frame. As conclusion, the paper will discuss the contribution of Arendt’s thoughts of people’s transcendence and its implications in facing the mob-rule.Key Words: constitutionalism, democracy, freedom, Hannah Arendt, revolution, totalitarianism